Keputusan Muktamar III Partai Persatuan Pembangunan. - Partai Persatuan Pembangunan (Indonesia). Muktamar 1994 : Jakarta, Indonesia); Partai Persatuan Pembangunan (Indonesia). Dewan Pimpinan Pusat (Jakarta : Dewan Pimpinan Pusat Partai Persatuan Pembangunan, 1994)
Decisions of a meeting of the United Development Party, a Muslim based political party in Indonesia.
Keywords: Partai Persatuan Pembangunan (Indonesia) -- Congresses; Indonesia -- Politics and government -- 20th century -- Congresses